Stride length-velocity relationship during running with body weight support - John A. Mercer; Carmen Chona (Elsevier, 2015)
Background: Lower body positive pressure (LBPP) treadmills can be used in rehabilitation programs and/or to supplement run mileage in healthy runners by reducing the effective body weight and impact associated with running. The purpose of this study is to determine if body weight support influences the stride length (SL)-velocity as well as leg impact acceleration relationship during running. Methods: Subjects (n = 10, 21.4 ± 2.0 years, 72.4 ± 10.3 kg, 1.76 ± 0.09 m) completed 16 run conditions consisting of specific body weight support and velocity combinations. Velocities tested were 100%, 110%, 120%, and 130% of the preferred velocity (2.75 ± 0.36 m/s). Body weight support conditions consisted of 0, 60%, 70%, and 80% body weight support. SL and leg impact accelerations were determined using a light-weight accelerometer mounted on the surface of the anterior-distal aspect of the tibia. A 4 × 4 (velocity × body weight support) repeated measures ANOVA was used for each dependent variable (α = 0.05). Results: Neither SL nor leg impact acceleration were influenced by the interaction of body weight support and velocity (p > 0.05). SL was least during no body weight support (p < 0.05) but not different between 60%, 70%, and 80% support (p > 0.05). Leg impact acceleration was greatest during no body weight support (p < 0.05) but not different between 60%, 70%, and 80% support (p > 0.05). SL and leg impact accelerations increased with velocity regardless of support (p < 0.05). Conclusion: The relationships between SL and leg impact accelerations with velocity were not influenced by body weight support.